Facilitation by ecosystem engineers enhances nutrient effects in an intertidal system. Issue 12 (22nd December 2017) - Eriksson, Britas Klemens; Westra, Joëlle; van Gerwen, Imke; Weerman, Ellen; van der Zee, Els; van der Heide, Tjisse; van de Koppel, Johan; Olff, Han; Piersma, Theunis; Donadi, Serena
Abstract: Ecosystem engineering research has recently demonstrated the fundamental importance of non‐trophic interactions for food‐web structure. Particularly, by creating benign conditions in stressful environments, ecosystem engineers create hot beds of elevated levels of recruitment, growth, and survival of associated organisms; this should fuel food webs and promote production on the ecosystem scale. However, there is still limited empirical evidence of the influence of non‐trophic interactions on the classical food‐web processes that determine energy transfer, that is, consumer–resource interactions. On the basis of a biomanipulation experiment covering 600 m 2 of an intertidal flat, we show that ecosystem engineers influence resource uptake efficiency and the accumulation of algae following nutrient enrichment in a soft‐sediment food web. Nutrient additions increased chlorophyll a concentrations in the sediment by 90%, but only in plots where we also introduced high densities (2000 per m 2 ) of a burrowing bivalve, the common cockle Cerastoderma edule . The artificial cockle beds increased the nutrient uptake efficiency of the biofilm and promoted sediment accumulation, which suggests that the cockles facilitated the sediment‐living algae by increasing sediment stability. This indicates that ecological interactions, rather than the availability of nutrients per se, set the limits for production in this coastal ecosystem. Our results emphasize the need to include facilitation theory and recognize that positive interactions between species are key to understand, manage, and restore ecosystems under human influence.